2022
DOI: 10.1027/1015-5759/a000655
|View full text |Cite
|
Sign up to set email alerts
|

The Nomological Network of the Short Dark Tetrad Scale (SD4)

Abstract: Abstract. The present study examined the nomological network of the Short Dark Tetrad scale (SD4). The SD4 measures narcissism, psychopathy, Machiavellianism, and sadism. We translated the original English SD4 into German and used an online sample ( N = 594, 77% women) to investigate its nomological network with regard to the Big Five, honesty-humility, maladaptive personality traits, impulsivity, aggression, motives, values, sociosexual orientation, the octants of the interpersonal circumplex model, and self-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 57 publications
12
57
0
Order By: Relevance
“…At the same time, they aimed for an economical measurement instrument. In Blötner et al (2021), the SD4 Mach revealed similar associations with the problematic criteria as the MaaQ did in our present study. Thus, we conclude that the MaaQ contributed to a better differentiation, provided theoretically sound explanations, warrants reasonable reliabilities for the respective scores (Cronbach’s αs from .73 to .78 for both studies), and is just as economical as other Mach scales or even more economical (MaaQ: 8 items, combined; SD4 Mach: 7 items; TDMS: 12 items; MPS: 16 items).…”
Section: Discussion Study 2 and General Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…At the same time, they aimed for an economical measurement instrument. In Blötner et al (2021), the SD4 Mach revealed similar associations with the problematic criteria as the MaaQ did in our present study. Thus, we conclude that the MaaQ contributed to a better differentiation, provided theoretically sound explanations, warrants reasonable reliabilities for the respective scores (Cronbach’s αs from .73 to .78 for both studies), and is just as economical as other Mach scales or even more economical (MaaQ: 8 items, combined; SD4 Mach: 7 items; TDMS: 12 items; MPS: 16 items).…”
Section: Discussion Study 2 and General Discussionsupporting
confidence: 89%
“…We measured Mach with the MaaQ (see Study 1), our German translation of the Two-Dimensional Machiavellianism Scale (TDMS; Monaghan et al, 2020), and the seven-item Mach scale from the German SD4 (Blötner et al, 2021). The TDMS assesses Machiavellian Views and Machiavellian Tactics with six items each.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that all CFIs in the analyses of MI indicated less than acceptable fit (< .90), whereas all RMSEAs were acceptable (< .08; Hu & Bentler, 1999). However, these findings are consistent with earlier analyses of the SD4 (Blötner et al, 2021;Neumann et al, 2021;Paulhus et al, 2020) 2009). By allowing marginal cross-loadings, ESEMs accounted for acceptable fit, CFIs = .90 and .91 in the US and German samples, respectively, both RMSEAs = .04.…”
Section: Exploratory Structural Equation Modelsupporting
confidence: 85%
“…The article entitled “The nomological network of the Short Dark Tetrad Scale (SD4)” by Christian Blötner, Matthias Ziegler, Caroline Wehner, Mitja D. Back, & Michael P. Grosz ( European Journal of Psychological Assessment , 1–11, https://doi.org/10.1027/1015-5759/a000655) has now been published as an open access article with “© The Author(s)” and under a CC BY-NC 4.0 license.…”
mentioning
confidence: 99%